Evaluation of Land Suitability for Sugarcane (Saccharum officinarum L.) in Banyuroto, Nanggulan Subdistrict, Kulonprogo Regency, Yogyakarta - Rizky Ahmad Al Farezi; Anna Kusumawati; Adiprasetya Widyatama; Lintang Pambayun (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The government has launched a sugar self-sufficiency program to increase sugarcane production. One of the strategies is land extensification by opening and managing new areas based on land suitability that meets the growth requirements of sugarcane. This research aims to identify the land suitability in Banyuroto Village for sugarcane (Saccharum officinarum L.). The research was conducted from February to May 2024 in Banyuroto Village, Nanggulan Subdistrict, Kulonprogo Regency, Yogyakarta. This study used a descriptive exploratory method with a field survey approach to identify land characteristics and evaluate the level of land suitability. Location points were determined using a purposive method with two Land Map Units (LMU) in Sambiroto and Kesoh hamlets. Soil sampling at each LMU was carried out using simple random sampling. Rainfall and air temperature data were obtained from the Meteorology, Climatology, and Geophysics Agency (BMKG) for the period 2019–2023. Observed land characteristics include soil texture, drainage conditions, effective soil depth, soil pH, cation exchange capacity (CEC), organic C content, total nitrogen (N-total), available phosphorus (P-available), percentage of surface rocks, and slope gradient. Calculation and determination of land suitability class, using the matching method, by comparing observed climate and land characteristics with sugarcane growing requirements based on land suitability evaluation criteria. The results show that Banyuroto Village, Nanggulan District, Kulon Progo, has an actual suitability class of S3oa,na for sugarcane cultivation, which means marginally suitable for sugarcane cultivation, with limiting factors being soil drainage and available nutrients. This is likely the cause of less-than-optimal sugarcane productivity. If improvements have been made, such as through soil cultivation (plowing), the creation of an intensive drainage system, and proper KCl fertilizer management, it has the potential to become a suitability class of S2 (fairly suitable).